Effects of dietary supplementation with bile acids on growth performance, antioxidant capacity, lipid metabolism, and cecal microbiota of Danzhou chickens - Xilong Yu; Ting Cao; Euphrème Ipemba; Ghislain Boungou Bakala; Lessebe Gambou Dieu Leveut; Weiqi Peng; Fengjie Ji; Hanfeng Li; Liangmei Xu; Hongzhi Wu (Poultry Science, 2025)
This study aimed to evaluate the effects of different bile acid levels in the diet on the growth performance, hepatic lipid metabolism, antioxidant capacity, and cecal microbiota of Danzhou chickens. 480 one-day-old male Danzhou chickens were randomly divided into four treatments and fed diets supplemented with 0, 200, 400, or 800 mg/kg bile acids. The trial lasted for 35 days. The results indicated that supplementing the diet with 400 mg/kg bile acids significantly increased average daily weight gain and reduced the feed conversion ratio (P < 0.05). Bile acid supplementation modulated serum lipid profiles, with 800 mg/kg increasing total bile acid levels, while 400 mg/kg reduced triglyceride and total cholesterol concentrations (P < 0.05). In the liver, 400 mg/kg bile acids increased total bile acid content, reduced triglycerides and total cholesterol accumulation, upregulated phospholipase C delta 1, acyl-CoA oxidase 1, and apolipoprotein A1 expression, and enhanced hepatic lipase and lipoprotein lipase activities (P < 0.05), indicating alleviated lipid deposition. All bile acids treatments improved antioxidant capacity by elevating total antioxidant capacity, catalase, superoxide dismutase, and glutathione peroxidase levels (P < 0.05) while reducing malondialdehyde (P < 0.05) in serum and liver, with optimal effects at 400 mg/kg. Bile acid supplementation increased levels of immunoglobulins (IgA and IgG) and the anti-inflammatory cytokine IL-10 (P < 0.05), while reducing levels of the pro-inflammatory cytokine IL-1β (P < 0.05). Morphological analysis of the intestine revealed that 400 mg/kg of bile acids significantly enhanced villus height and the villus height-to-crypt depth ratio (P < 0.05) in both the duodenum and ileum. Cecal microbiota analysis revealed that supplementation with 400 mg/kg bile acids increased microbial diversity and enriched Christensenellaceae_R-7_group and Weissella, whereas Barnesiellaceae_unclassified, Campylobacter, and Lactobacillus were predominant in the CON. In conclusion, the results suggest that dietary supplementation with 400 mg/kg of bile acids enhances antioxidant capacity and immune function in Danzhou chickens, potentially improving serum and hepatic lipid metabolism by modulating the cecal microbiota, thereby promoting growth performance.